(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
Urban centers in Nigeria served as the sites of enchanting challenges and diverse spectacles. In this regard, the city of Lagos became the site of diverse experiments and strategies in urban livelihood. Though there is an assumption that livelihood is about the ways and means of “making a living”, it also about creating and embracing new opportunities. While gaining livelihood, or attempting to do so, people may, at the same time have to cope with risks and uncertainties, such as a wide range of forces, social , economic, political, legal and environmental and institutional both within and outside the locality in which a household lives. It is within this conceptualization that this paper examines human smuggling and traffic-in persons, migration, sexual trade, currency trafficking, armed robbery and forced labour between Nigeria and Benin Republic. These are global problems, not limited to Nigeria and Benin, since the criminal networks cut across nations. Poverty, unemployment and corruption, no doubt, are known triggers, contributing to observed cross-border security challenges in both Nigeria and Benin Republic. This study interrogates the neglected aspects of cross-border security challenges, especially those connected to livelihood and survival. It raises posers as to why and how the criminalized livelihood means are sustained? What can be done to transform or reverse this trend? The study relied on both primary and secondary sources. Primary data included oral interviews, newspaper and archival materials. Secondary sources were obtained from university libraries and research institutes spread across Nigeria. Data were historically analyzed. This study concludes that inequalities, deprivation, poverty and corruption in Nigeria and Benin Republic served as impetus to the emergence and development of cross-border security challenges. Thus, it proffers that good governance through human security approach, equitable distribution of income and social security, rather than the law enforcement is a preferred solution to the problems of unlawful migrations, cross-border prostitutions, currency trafficking, smuggling and armed robbery.